Impact of Dienogest Alone or in Combination with Ethinylestradiol on the Quality of Life of Women with Endometriosis: A Prospective Cohort Study - Mujde Canday; Suleyman Salman (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aim to compare the effectiveness of oral contraceptives and dienogest, primarily by considering the quality of life scale. We also aim to compare the Cancer Antigen-125 and Anti-mullerian Hormone values.